2019
DOI: 10.3389/fmars.2019.00745
|View full text |Cite
|
Sign up to set email alerts
|

Observational Insight Into the Subsurface Anomalies of Marine Heatwaves

Abstract: Marine heatwaves (MHWs) are extreme ocean warming events that can have devastating impacts, from biological mortalities to irreversible redistributions within the ocean ecosystem. MHWs are an added concern because they are expected to increase in frequency and duration. To date, our understanding of these extreme ocean temperature events is mainly limited to the surface layers, despite some of the consequences they are known to have on the deep marine environment. In this paper, using data from sea surface tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
76
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 51 publications
6
76
1
Order By: Relevance
“…Subsurface temperature measurements might be more adequate to properly assess the impact of extreme heat events on ecosystems. Subsurface MHWs are likely to occur in most places with or without surface corresponding surface expressions (Elzahaby & Schaeffer, 2019; Schaeffer & Roughan, 2017). However, the ability to assess subsurface MHWs globally is limited by the sparsity and lack of continuity of such observations (Holbrook et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Subsurface temperature measurements might be more adequate to properly assess the impact of extreme heat events on ecosystems. Subsurface MHWs are likely to occur in most places with or without surface corresponding surface expressions (Elzahaby & Schaeffer, 2019; Schaeffer & Roughan, 2017). However, the ability to assess subsurface MHWs globally is limited by the sparsity and lack of continuity of such observations (Holbrook et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another spatial consideration is that our study mostly concerns the variability of sea‐surface properties. Recent studies using Argo floats have revealed the spatio‐temporal characteristics of marine heatwaves below the surface mixed layer that is distinct from their surface signal (Elzahaby & Schaeffer, 2019; Jackson, Johnson, Dosser, & Ross, 2018). Hence, investigating the vertical structures of marine heatwaves and associated biogeochemical properties (Zaba & Rudnick, 2016) would be worthwhile to comprehend the impacts throughout the water column.…”
Section: Discussionmentioning
confidence: 99%
“…[H2] Monitoring subsurface MHWs While remote sensing, in combination with surface drifting buoys and ship underway data, provides high resolution SST data for both historical and real-time analyses of MHW surface characteristics, it is not only surface properties that need attention. MHWs can also exhibit considerable depth penetration, or exist at depth with no surface expression, necessitating subsurface data 58,59 . Yet, the ability to characterise subsurface MHWs in both the open ocean 59 and coastal regions 58 is challenged by the sparsity of observations and the absence of continuous, long-term time-series in the historical record (such as data from eXpendable BathyThermograph (XBT), conductivity, temperature and depth (CTD), gliders, and Argo profiles).…”
mentioning
confidence: 99%
“…MHWs can also exhibit considerable depth penetration, or exist at depth with no surface expression, necessitating subsurface data 58,59 . Yet, the ability to characterise subsurface MHWs in both the open ocean 59 and coastal regions 58 is challenged by the sparsity of observations and the absence of continuous, long-term time-series in the historical record (such as data from eXpendable BathyThermograph (XBT), conductivity, temperature and depth (CTD), gliders, and Argo profiles). These challenges hinder the development of robust and spatially complete subsurface temperature climatologies needed for statistical assessments of MHWs.…”
mentioning
confidence: 99%
See 1 more Smart Citation